2017
DOI: 10.1111/1365-2745.12803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crown architecture and stand structure on light absorption in mixed and monospecificFagus sylvaticaandPinus sylvestrisforests along a productivity and climate gradient through Europe

Abstract: Kamil Bielak 5 | Andrés Bravo-Oviedo 6,7 | Lluis Coll 8 | Miren del Río 6,7 | Lars Drössler 9 | Michael Heym 10 | Václav Hurt 11 | Magnus Löf 9 | Jan den Ouden 12 | Maciej Pach 13 | Abstract 1. When tree-species mixtures are more productive than monocultures, higher light absorption is often suggested as a cause. However, few studies have quantified this effect and even fewer have examined which light-related interactions are most important, such as the effects of species interactions on tree allometric relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 56 publications
4
87
0
Order By: Relevance
“…We found that tree crown morphology was significantly influenced by interspecific versus intraspecific competition, which is consistent with studies showing that interspecific interactions affect species-specific allometric relationships (Forrester et al, 2017a;Pretzsch, 2014). Vertical crown extension of Maritime pine was greater in mixed versus pure stands, especially in larger trees (Fig.…”
Section: Crown Allometry Plasticity By Species Mixingsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that tree crown morphology was significantly influenced by interspecific versus intraspecific competition, which is consistent with studies showing that interspecific interactions affect species-specific allometric relationships (Forrester et al, 2017a;Pretzsch, 2014). Vertical crown extension of Maritime pine was greater in mixed versus pure stands, especially in larger trees (Fig.…”
Section: Crown Allometry Plasticity By Species Mixingsupporting
confidence: 90%
“…In this work, we found that over-yielding at the stand level was related to vertical structural heterogeneity (Table 5) resulting from species interaction, which increased mixed-species stand productivity more than in monocultures. In other words, crown complementarity in canopy space can be thought of as a complementary mechanism that links biodiversity with ecosystem productivity (Forrester et al, 2017a). Similar relationships have been observed in recent studies (Dănescu et al, 2016;Vallet and Perot, 2016;Williams et al, 2017).…”
Section: Ecological Explanation Of the Mixing Effects On Productivitysupporting
confidence: 79%
See 2 more Smart Citations
“…The original data set covers attributes at the tree level, increments cores, stand and triplet characteristics and has been used for different purposes by Pretzsch et al (2015Pretzsch et al ( , 2016, Río et al (2016bRío et al ( , 2017, Dirnberger et al (2016) and Forrester et al (2017). The data set presented here describes the original data, but ongoing projects can complement the published data by additional measurements of resource supply, nutritional status and wood properties.…”
Section: Reuse Potential and Limitsmentioning
confidence: 99%